Carbon footprint and cost analysis of a bicycle lane in a municipality - J. Prasara-A; A. Bridhikitti (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Cycling has been widely promoted as an alternative mode of transport to help the reduction of environmental impact and improve users' health. Promoting cycling will help enhance the "Green City" initiative in Thailand. While several studies have addressed social issues of cyclists, the environmental impacts and economic viability of cycling infrastructure are yet unknown. Quantifying its environmental impact and the costing aspect are essential to prove that cycling would positively affect a city. This study compares the expected environmental and economic impacts before and after constructing a bicycle lane in Mahasarakham, Thailand.METHODS: This study uses life cycle assessment and life cycle costing to assess a bicycle lane's environmental and economic viability. Life cycle assessment and life cycle costing are tools used to analyze environmental impact and cost during the life cycle of a product or service. The scope of this study covers the processing of raw material acquisition, transportation, construction, use, and disposal. The functional unit set for this study is the use of a bicycle lane for one year. The environmental impact examined is greenhouse gas emissions along the product's life cycle (the so-called "carbon footprint").FINDING: According to the results, approximately 0.2 million tons of carbon dioxide equivalent of carbon footprint could have been reduced in 2020 had a bicycle lane been installed. The use phase plays the leading role in reducing carbon footprint. The reduction in environmental impacts is due to reduced fuel consumption by cars and motorcycles when bicycles are used. Even though a low rate (26%) of road users, who participated in this research, were willing to ride bikes had a bicycle lane been provided, a considerable amount of environmental impact could still have been reduced.CONCLUSION: The carbon footprint expected to be reduced in a year is valued at about 4.7 million baht of carbon credit. In comparison, the life cycle cost of bicycle lanes for one year is approximately 3.7 million baht. Furthermore, it is anticipated that had a bicycle lane been installed since 2015, the city would have reduced overall carbon footprint emissions by more than 1.15 million tons of carbon dioxide equivalent by 2020. Therefore, the results of environmental impact and cost assessment from this study are helpful for urban environmental management.